The role of bystanders, first responders, and emergency medical service providers in timely defibrillation and related outcomes after out-of-hospital cardiac arrest: Results from a statewide registry. (November 2015) - Hansen, Carolina Malta; Kragholm, Kristian; Granger, Christopher B.; Pearson, David A.; Tyson, Clark; Monk, Lisa; Corbett, Claire; Nelson, R. Darrell; Dupre, Matthew E.; Fosbøl, Emil L.; Strauss, Benjamin; Fordyce, Christopher B.; et al.
Abstract: Aim: Defibrillation by bystanders and first responders has been associated with increased survival, but limited data are available from non-metropolitan areas. We examined time from 911-call to defibrillation (according to who defibrillated patients) and survival in North Carolina. Methods: Through the Cardiac Arrest Registry to Enhance Survival, we identified 1732 defibrillated out-of-hospital cardiac arrests from counties with complete case capture (population 2.7 million) from 2010 to 2013. Results: Most patients (60.9%) were defibrillated in >10 min. A minority (8.0%) was defibrillated <5 min; most of these patients were defibrillated by first responders (51.8%) and bystanders (33.1%), independent of location of arrest (residential or public). Bystanders initiated cardiopulmonary resuscitation (CPR) in 49.0% of cases and defibrillated 13.4% of those. Survival decreased with increasing time to defibrillation (<2 min: 59.1%; 2 to <5 min: 38.5%; 5–10 min: 33.1%; >10 min: 13.2%). Odds of survival with favorable neurologic outcome adjusted for age, sex, and bystander CPR improved with faster defibrillation (<2 min: OR 7.73 [95% CI 3.19–18.73]; 2 to <5 min: 3.78 [2.45–5.84]; 5–10 min: 3.16 [2.42–4.12]; >10 min: reference). Conclusion: Bystanders and first responders were mainly responsible for defibrillation within 5 min, independent of location of arrest. Bystanders initiated CPR in half of the cardiac arrest cases but only defibrillated a minority of those. Timely defibrillation and defibrillation by bystanders and/or first responders were strongly associated with increased survival. Strategic efforts to increase bystander and first-responder defibrillation are warranted to increase survival after out-of-hospital cardiac arrest.